Synthesis and Optical Properties of Phenanthroline‐Derived Schiff Base‐Like Dinuclear RuII–NiII Complexes. Issue 20 (5th January 2018) - Kurz, Hannah; Lochenie, Charles; Wagner, Kristina G.; Schneider, Sandra; Karg, Matthias; Weber, Birgit
Abstract: Two phenanthroline‐derived Schiff base‐like ligands with a covalently linked ruthenium(II) phosphorescent unit were synthesised and converted into bimetallic Ru II –Ni II complexes. The optical properties were studied to examine a possible photoluminescence quenching through a nonradiative energy‐transfer upon a coordination‐induced spin‐state switch (CISSS) at the nickel(II) centre. Therefore, the metalloligands and the nickel(II) complexes were studied using UV/Vis absorbance, steady‐state, and time‐resolved emission spectroscopy in solutions of MeCN and pyridine. It is demonstrated that the nature of the bridging ligand between the ruthenium(II) donor and the nickel(II) acceptor strongly influences the photophysical behaviour upon CISSS. For the complex with a phenazine bridge, photoluminescence quenching is observed in the presence of a paramagnetic nickel(II) centre. Abstract : A multifunctional switch : The photophysical properties of phenantroline‐derived dinuclear Ru II –Ni II complexes as function of the spin state at the nickel(II) centre, modified by coordination‐induced spin‐state switch (CISSS) are investigated (see picture; py=pyridine).